Multifunctional landscapes - International Livestock Research Institute (International Livestock Research Institute, 2024)
We urgently need to invest in multifunctional landscapes to combat biodiversity loss, desertification, and climate change. By showcasing practices like agroforestry, wetland restoration, and sustainable agriculture, this film emphasizes the power of integrated solutions to protect ecosystems, restore land, and mitigate climate change - all aligned with the goals of the three Rio Conventions.